1971
DOI: 10.1002/pol.1971.160091003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of molecular weight on the refractive increment of polyethylene and n‐alkanes

Abstract: synopsisAs in the case with other polymers previously reported, the values of the refractive index increment dn/dc of polyethylene and the n-alkanes change with molecular weight. Most of the variation may be understood by examination of the role of density in the Lorentz-Lorenz mixing equation ior specific refractivity, R12 = plR1 + P2R2 used to calculate dnldc. It rcay also be shown that as the absolute refractive index difference between solute and solvent becomes smaller, dnldc becomes more sensitive to den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1978
1978
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Molecular weight dependencies of dn / dc were reported experimentally, which are expressed as linear functions of reciprocal number‐average molecular weight 5–10. However, it should be verified that the molecular weight dependency is also expressed as a linear function of reciprocal molecular weight of each component (see the ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular weight dependencies of dn / dc were reported experimentally, which are expressed as linear functions of reciprocal number‐average molecular weight 5–10. However, it should be verified that the molecular weight dependency is also expressed as a linear function of reciprocal molecular weight of each component (see the ).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, in the oligomeric region, a number of studies have shown that dn / dc greatly depends on the molecular weight 1–10. Variations in dn / dc affect not only the accuracy of M w measured by SLS, but also that of molecular weight distribution measured by size‐exclusion chromatography (SEC).…”
Section: Introductionmentioning
confidence: 99%
“…Ao is the wavelength in vacuum of the scallered light, set at 546 nm in this work , nand nB are the indices of refra ction of the solvent and benzene, taken as 1.586 [8] and 1.503 [3], respectivel y, dn/dc is the differential refractive index of the solution, measured as described in 3.1, N A is Avogadro's number, taken as 6.022 X 10 23 mol -I, Vv B is the Rayleigh ratio for the vertically polarized scattering of vertically polarized light from benzene, used for calibration and obtained as described in the following paragraph, and S is the measured ratio I G/I B of the scattering signal obtained from the glass working standard to that obtained from benzene.…”
Section: Differential Refractive Indexmentioning
confidence: 99%
“…The UV detector, Wyatt Dawn EOS, and refractive index detector were aligned using an injection of 0.50 mg bovine serum albumin monomer fractionated by a Superdex 200 10/300 GL gel permeation column. Alkylated bPEI and 1,4-bis-maleimidobutane-containing dendrimer constructs were analyzed using three PSS Novema columns in series: a guard column, a 300 Å 8×300 mm column, and a 1,000 Å 8×300 mm column (38). All samples were dissolved in 1% aqueous formic acid filtered through a 0.2 μm pore size filter and eluted with the same solvent.…”
Section: Size-exclusion Chromatography With Detection By Static Lightmentioning
confidence: 99%
“…To allow mass measurements, the Altex 156 refractive index detector was calibrated using five sodium chloride concentrations known to the fourth significant digit (e.g., 0.1847 mg/mL) spanning the range of 0.0000-2.000 mg/mL (NaCl specific refractive index increment, dn/dc=0.172 mL/g) (38). The Wyatt Dawn EOS 18-angle detectors were normalized using spectrophotometric grade toluene.…”
Section: Size-exclusion Chromatography With Detection By Static Lightmentioning
confidence: 99%